HR innovation in mediating entrepreneurial motivation in improving the competitive ability of Palu Fried Onions MSMEs - Ibrahim, Andi Indriani; Setiawan, Margono; Noermijati; Rahayu, Mintarti (Business, Management and Economics Engineering, 2024)
Purpose – This study aims to describe the competitive ability of MSMEs Palu Fried Onions (BGP) from the point of view of human resources, namely innovation and the influence of motivation.Research methodology – This research was conducted on 141 active BGP MSMEs in Palu and tested using quantitative methods using SEM-PLS analysis testing.Findings – The study results show that Human Resource Innovation is proven to affect the ability of the Palu Fried Onions MSMEs.Research limitations – A limitation of this study is that it focuses solely on the competitive abilities of BGP MSMEs from the perspective of human resources, specifically innovation and motivation, and does not explore other potential factors that might influence their competitiveness.Practical implications – The results of this study have the benefit of being practical considerations for driving BGP MSMEs to increase their competitiveness; besides that, the results of this study also expand the variation of the Diamond Model or the Diamond Model of production factors to be competitive.Originality/Value – Rather than focusing solely on traditional factors, this research delves into the innovative realm of human resource innovation and motivation as key drivers of competitiveness.